2014
DOI: 10.1039/c4cp03549f
|View full text |Cite
|
Sign up to set email alerts
|

Remarkable enhancement of the photoreactivity of a polyfluoroalkyl azobenzene derivative in an organic–inorganic nano-layered microenvironment

Abstract: Organic-inorganic hybrids composed of polyfluoroalkyl azobenzene surfactant (abbreviated as C3F-Azo-C6H) and inorganic layered compounds are able to undergo reversible three-dimensional morphology changes such as interlayer space changes and nanosheet sliding in a giant scale due to reversible trans-cis isomerization of the azobenzene moiety upon photo-irradiation. In this paper, we have systematically studied the relationship between the layered hybrid microstructures of C3F-Azo-C6H-clay and their photoreacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…The complete cis-to-trans transition is hardly realized for azobenzene compounds because of the overlap of the n−π* transition of the trans and cis isomers. , We confirmed the back-isomerization reaction for all of our samples, but the extent depended on the SL structure. Tentatively, we attribute this observation to the fact that the SL structure is likely to affect the optical band gap and, thereby, the activation energy of the cis-to-trans reaction . This will be systematically studied in our already initiated future work.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…The complete cis-to-trans transition is hardly realized for azobenzene compounds because of the overlap of the n−π* transition of the trans and cis isomers. , We confirmed the back-isomerization reaction for all of our samples, but the extent depended on the SL structure. Tentatively, we attribute this observation to the fact that the SL structure is likely to affect the optical band gap and, thereby, the activation energy of the cis-to-trans reaction . This will be systematically studied in our already initiated future work.…”
Section: Resultsmentioning
confidence: 95%
“…Tentatively, we attribute this observation to the fact that the SL structure is likely to affect the optical band gap 43 and, thereby, the activation energy of the cis-to-trans reaction. 67 This will be systematically studied in our already initiated future work.…”
Section: Resultsmentioning
confidence: 97%
“…Mallouk and colleagues established a method to encapsulate ionic dye molecules electrostatically with a layered silicate and an ionic polymer, and they found that the color could be changed by tuning the intramolecular interactions with the polymer. , Takagi and colleagues realized color tuning on a layered silicate by combining dye molecules and the layered silicate. , They also found that emission from dye molecules was enhanced on the surface of layered silicates. Sasai and colleagues added surfactants onto the surface of layered silicate to improve the emission of rhodamine 6G. , Bard and Mallouk , reported that electrodes modified with a layered silicate concentrated a redox-active compound for electrochemical and photoelectrochemical measurements. Modification of electrodes with a layered silicate via Langmuir–Blodgett film preparation methods was reported by Yamagishi and colleagues for use in pyroelectricity and has also been used for magnetism. , For photofunctional applications, the enhancement of photoisomerization, photodimerization, , and photostabilization on layered silicates has been reported.…”
Section: Introductionmentioning
confidence: 99%
“…An inorganic nanosheet prepared by exfoliation from a layered microcrystal has also been expected to be one of the most promising materials providing the microenvironment for supramolecular systems and molecular assemblies because of their characteristics such as the extensively wide and smooth surface area, surface positive/negative charge, flexible interlayer distance, and intercalation ability of functional molecules into the interlayer spaces. In particular, an organic/inorganic hybrid composed of photo-responsive molecule and inorganic nanosheet is a curious supramolecular system coupled with the nanosheet microenvironment to express various photo-functions such as fluorescence enhancement, highly efficient excitation energy transfer , and chemical reactions, photocatalysis, , artificial photosynthesis, photo-activated actuator materials, ,, and so on. It is also noteworthy that further improvement and novel expression of photo-functions have been expected by controlling the dimensionality of nanosheet systems between an exfoliated single nanosheet, stacked nanosheets, nanoscroll, and nanoscroll aggregates. ,, …”
Section: Introductionmentioning
confidence: 99%